a3 + b3 = ( a+b) ( a2 – ab + b2 )
a3 +
= ( a+
) ( a2 – a.
+
)
= ( a+
) ( a2 +
– 1 )
= ( a+
) ( 14 – 1)
= 13 ( a+
) …………………………………………………(i)
a2 +
= 14
or, ( a +
)2 – 2.a.
= 14
or, ( a +
)2 – 2 = 14
or, ( a +
)2 = 14+2
or, ( a +
)2 = 16
or, ( a +
)2 = 42
or, ( a +
) = 4
Put the value in (i) equation then we get,
a3 +
=13 ( a+
)
= 13 . 4
= 52
a2 +
= 14 then a3 +
= ?
- 13
- 54
- 52
- 4
Hints : a3 + b3 = ( a+b) ( a2 – ab + b2 )
a3 + b3 = ( a+b) ( a2 – ab + b2 )
a3 +
= ( a+
) ( a2 – a.
+
)
= ( a+
) ( a2 +
– 1 )
= ( a+
) ( 14 – 1)
= 13 ( a+
) …………………………………………………(i)
a2 +
= 14
or, ( a +
)2 – 2.a.
= 14
or, ( a +
)2 – 2 = 14
or, ( a +
)2 = 14+2
or, ( a +
)2 = 16
or, ( a +
)2 = 42
or, ( a +
) = 4
Put the value in (i) equation then we get,
a3 +
=13 ( a+
)
= 13 . 4
= 52
a3 + b3 = ( a+b) ( a2 – ab + b2 )
a3 +
= ( a+
) ( a2 – a.
+
)
= ( a+
) ( a2 +
– 1 )
= ( a+
) ( 14 – 1)
= 13 ( a+
) …………………………………………………(i)
a2 +
= 14
or, ( a +
)2 – 2.a.
= 14
or, ( a +
)2 – 2 = 14
or, ( a +
)2 = 14+2
or, ( a +
)2 = 16
or, ( a +
)2 = 42
or, ( a +
) = 4
Put the value in (i) equation then we get,
a3 +
=13 ( a+
)
= 13 . 4
= 52